The performance of Latin American diplomats in the rescue of Jews during the World War II - Zadoff, Efraim (Cuadernos Judaicos, 2019)
The attitude of Latin America countries towards the Jews during the Shoah took place at two levels: the immigration possibilities -officially or unofficially- that these countries gave to Jewish refugees from 1933 to 1945; the granting of passports that could protect Jews from persecution, deportation and extermination. This work is part of a broader investigation dealing with the second issue. Generally the action of granting passports to save Jews was assumed by some Latin American diplomats without consulting with their governments and sometimes against their policy. Some of them risked and lost his career by this purely humanitarian action. So far this research has been conducted on the consuls from Ecuador, Manuel Antonio Munoz Borrero; from El Salvador, Jose Arturo Castellanos, and Perú, José Maria Barreto, the three recognized by Yad Vashem as Righteous Among the Nations. Also here I present the intermediate results of my research about Samuel del Campo, business manager and representative of Chile in Romania. My aim is to continue researching to find out the attitude of other consuls, as Rodolfo Hügli of Paraguay, José Gambetta of Peru, Max Brunner Haiti, Dominican Alfonso Bauer, among others. My intention is to study and get to know the performance of these consuls and their context, to verify whether, as the cases of Munoz Borrero, Castellanos and Barreto, also will have for them a vindication and recognition for their action in order to save lives of fellow human beings.